PENGARUH KOMPETENSI, INDEPENDENSI, DAN PENGALAMAN TERHADAP KUALITAS AUDIT DENGAN DUE PROFESIONAL CARE SEBAGAI VARIABEL INTERVENING PADA INSPEKTORAT DI KABUPATEN SIAK DAN KUANTAN SINGINGI - Yulia, Yulia; Hasan, Amir; Hardi, Hardi (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
This study was conducted to test empirically 1) Effect of competence, independence and experience of the due professional care, 2) Influence of competence, independence, experience and due professional care directly on audit quality 3) Effect of competence, independence, and experience on audit quality through professional due care as an intervening variable. Object under investigation is the Inspectorate in Siak And Singingi Kuantan.Tests conducted by the path analysis, using SPSS version 21. Prior to the tests, conducted prior testing data quality (reliability and validity), test data normality and linearity test. The results of this study indicate that 1) the competence, independence and experience, each has positive influence on professional due care. 2) competence, independence and experience, each of which has no direct influence on the quality of the audit, due professional care while the effect on audit quality. 3) Competence, independence and experience, each effect on audit quality through professional due care as an intervening variable.